2017
DOI: 10.3389/fendo.2017.00121
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Biochemical Alterations in Brown and Subcutaneous White Adipose Tissues of Mice Using Fourier Transform Infrared Widefield Imaging

Abstract: Stimulating increased thermogenic activity in adipose tissue is an important biological target for obesity treatment, and label-free imaging techniques with the potential to quantify stimulation-associated biochemical changes to the adipose tissue are highly sought after. In this study, we used spatially resolved Fourier transform infrared (FTIR) imaging to quantify biochemical changes caused by cold exposure in the brown and subcutaneous white adipose tissues (BAT and s-WAT) of 6 week-old C57BL6 mice exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Aqueous metabolites were resolubilized in 600 μL of deuterium oxide buffered to a pH of 7.4 and containing 0.16-mM 3-(trimethylsilyl)propionic-2,2,3,3 acid as a quantitative reference [ 68 ]. Adipose tissue (~20 mg) was extracted following a slightly modified MTBE extraction that is specifically used for adipose samples [ 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…Aqueous metabolites were resolubilized in 600 μL of deuterium oxide buffered to a pH of 7.4 and containing 0.16-mM 3-(trimethylsilyl)propionic-2,2,3,3 acid as a quantitative reference [ 68 ]. Adipose tissue (~20 mg) was extracted following a slightly modified MTBE extraction that is specifically used for adipose samples [ 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…The similar conclusions were made by other authors as well. The FTIR results of the studies [80,81] demonstrated that there were several alterations in the triglyceride spectral region of SAT and VAT of male obese mice. The authors [82] have used FTIR spectroscopy to investigate the composition of fatty acid of adipose tissue in men having the metabolic syndrome.…”
Section: Ftir and Raman Spectroscopiesmentioning
confidence: 99%
“…The procedure for sample preparation has been described explicitly elsewhere 23 , 33 . Briefly, Male C57BL6 mice (Jackson Laboratories) were housed in standard caging with 12 hour light: dark cycle, and food and water provided ad libitum .…”
Section: Methodsmentioning
confidence: 99%
“…The study of the bio-molecular alterations in the biochemistry of retinal layers with different duration of diabetes would be greatly facilitated by vibrational spectroscopic techniques without any need for isolating the cell compartments. FT-IR chemical imaging has been used to investigate various tissue types including adipose 23 , prostate 24 , breast 25 , 26 , kidney 27 , brain 28 , 29 , pancreas 30 , pleura 31 , and colon 32 .…”
Section: Introductionmentioning
confidence: 99%